The Effect of Climate and Diet on Body Lipid Composition in the Oriental Hornet (Vespa orientalis) - Volov, Mika; Cohen, Nitzan; Bodner, Levona; Dubiner, Shahar; Hefetz, Abraham; Bouchebti, Sofia; Levin, Eran (Frontiers in Ecology and Evolution, 2021)
Fatty acids (FA) are the primary metabolic fuel for many organisms and the fundamental component of membranes of all living organisms. FAs can be saturated (SFA), monounsaturated (MUFA), or polyunsaturated (PUFA). PUFA are not synthesized by most animals and are considered as essential nutrients. We examined the effect of climate on the saturation level of polar (mostly membranal) and neutral lipids in the body of the Oriental hornet (Vespa orientalis) from two extreme climatic zones: Mediterranean high elevation; and hot arid desert. In contrast to previous reports, the environmental temperature was shown to affect the hornet colonies' thermal environments. The hornets nonetheless maintained their colony temperature within a narrow range. Analyses of the hornets' unsaturation levels of polar and non-polar body lipids revealed caste differences: gynes and males contained less unsaturated lipids than workers. However, there were no differences in the respective castes between the two different climate zones tested. Experimentally manipulating the diet of queenless hornet colonies to a high Omega-3 diet (salmon) or a high Omega-6 diet (crickets) had only a minor effect on the worker-born males’ lipid composition. Although salmon-fed males had a higher Omega-3 content than cricket-fed ones, the proportion of these fatty acids was still low (below 1%). Cricket-fed males had significantly higher levels of Omega-6 than salmon-fed males. Our data show that the specific lipid composition of the hornet body is highly regulated and deficient in essential PUFA, even under different climates or high Omega-3 or Omega-6 PUFA diet. PUFA, especially Omega-3, is considered to have a beneficial effect on physiological processes. Our finding that these FA, when common in the diet, are almost absent in the body raises questions about how they affect animals' physiology.